Clinical and Laboratory Diagnosis of Buruli Ulcer Disease: A Systematic Review - Samuel A. Sakyi; Samuel Y. Aboagye; Isaac Darko Otchere; Dorothy Yeboah-Manu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Buruli ulcer (BU) is a necrotizing cutaneous infection caused by Mycobacterium ulcerans. Early diagnosis is crucial to prevent morbid effects and misuse of drugs. We review developments in laboratory diagnosis of BU, discuss limitations of available diagnostic methods, and give a perspective on the potential of using aptamers as point-of-care. Methods. Information for this review was searched through PubMed, web of knowledge, and identified data up to December 2015. References from relevant articles and reports from WHO Annual Meeting of the Global Buruli Ulcer initiative were also used. Finally, 59 articles were used. Results. The main laboratory methods for BU diagnosis are microscopy, culture, PCR, and histopathology. Microscopy and PCR are used routinely for diagnosis. PCR targeting IS2404 is the gold standard for laboratory confirmation. Culture remains the only method that detects viable bacilli, used for diagnosing relapse and accrued isolates for epidemiological investigation as well as monitoring drug resistance. Laboratory confirmation is done at centers distant from endemic communities reducing confirmation to a quality assurance. Conclusions. Current efforts aimed at developing point-of-care diagnostics are saddled with major drawbacks; we, however, postulate that selection of aptamers against MU target can be used as point of care.